Peningkatan Kemampuan Berpikir Kreatif untuk Guru SD Negeri 10 Lambung Bukit Melalui Penulisan Cerita Anak - Ria Febrina; Aslinda Aslinda; Efri Yades; M Yusuf; Ronidin Ronidin; Elly Delfia; Armini Arbain (Warta Pengabdian Andalas, 2019)
Teachers as educators likely require great encouragement such crative thinking ability. The monotonous teachers routines such as cumulative credits fulfillment or teaching hours force the ability decrease on teachers to think creatively. Therefore, this community service activity is succesfully carried out toward SD N Lambung Bukit teachers with theme “Peningkatan Kemampuan Berpikir Kreatif untuk Guru SD Negeri 10 Lambung Bukit melalui Penulisan Cerita Anak”. This given training presents the theories and practices about creative writing then later the teachers are able to produce the creative stories for children. The are three methods are conducted in this activity, those are lecture method, the discussion method, and the practical method of writing children's stories. To find out the creative thinking and writing abilities of SD Negeri 10 Lambung Bukit, at the end of the training, an evaluation is also applied to criticize the language and ideas that the teachers put on their works. Based on this training, those children's stories still contain Indonesian spelling mistakes, such as writing letters, writing punctuation marks, and writing loanwords elements. However, the SD Negeri 10 Lambung Bukit teachers have experienced in improving the creative thinking, especially in the choice of children's story ideas, the choice of diction, and the composition of effective sentences that written in accordance with Indonesian language rules.